Effects of Meaningful Action Observation Therapy on Occupational Performance, Upper Limb Function, and Corticospinal Excitability Poststroke: A Double-Blind Randomized Control Trial. (16th September 2022) - Shamili, Aryan; Hassani Mehraban, Afsoon; Azad, Akram; Raissi, Gholam Reza; Shati, Mohsen
Abstract : Introduction . Action observation therapy (AOT) is a mirror neuron-based approach that has been recently used in poststroke rehabilitation. The main goal of this study was to investigate the effectiveness of AOT of occupations and tasks that are meaningful for chronic stroke patients on occupational performance, upper-extremity function, and corticospinal changes. Method . A randomized control trial was designed to compare between experimental (n = 13 ) and control groups (n = 14 ). In both groups, the execution of meaningful tasks was practiced, but the videos of those tasks were just shown to the experiment group. Instead, patients in the control group watched nature videos as a placebo. Clinical outcomes were evaluated using the Canadian Occupational Performance Measure (COPM), Fugl-Meyer Assessment (FMA), Action Research Arm Test (ARAT), and Box-Block Test (BBT) on 3 occasions: baseline, post (at 4 weeks), and follow-up (at 8 weeks). The assessments of central motor conduction time (CMCT) for abductor policis brevis (APB) and extensor indicis (EI) were only recorded at baseline and posttreatment. Both assessors of clinical and neurophysiological outcomes were blinded to the allocation of subjects. Result . Finally, the results of outcomes in 24 patients who completed the study were analyzed. In both groups, significant improvements after treatment were seen for most outcomes (p ≤ 0.05 ). These changes were persistent until follow-up. There were significant differences in COPM performance (p = 0.03 ) and satisfaction (p = 0.001 ) between the experimental and control groups. In contrast, other clinical assessments such as FMA, ARAT, and BBT did not show significant differences between the two treatments (p ≥ 0.05 ). The results of CMCT related to APB showed a more significant change in the experiment group compared to the control group (p = 0.022 ). There was no difference in change detected between the two groups for CMCT related to EI after treatments. Conclusion . Observation and execution of meaningful activities can enhance the effects of simply practicing those activities on occupational performance/satisfaction and corticospinal excitability poststroke.